The evolution of vision in nascent stage entrepreneurship - Egwuonwu, O.; Simaens, A. (EURAM 2020 (European Academy of Management) Conference, 2020)
The majority of leadership and entrepreneurial literature affirms the importance of vision in entrepreneurship. However, to date, there is an absence of research that sufficiently describes the evolution of entrepreneurial vision in nascent stage entrepreneurship. This paper explores the evolution of nascent stage entrepreneurial vision. Participants in a pre-seed accelerator program, in Lisbon, Portugal reported on their entrepreneurial journey as it unfolded over one-week of entrepreneurial activity. Utilizing an inductive approach that combines the Experience Sampling Method (ESM) with semi-structured interviews, we investigate how nascent entrepreneurs define vision, perceive their leadership role, and are influenced by their vision for their ventures. Findings suggest that 1. entrepreneurial vision in nascent entrepreneurs is perceived as future-oriented, solution-based, and differentiated outcome-focused. 2. nascent entrepreneurs perceive themselves to be “Leaders of Vision”. 3. five emerging realities influence the evolution of nascent stage entrepreneurial vision: customer reality, technological reality, social reality, self-sovereign reality, and competitive reality. These findings contribute to the research at the intersection of entrepreneurial leadership and entrepreneurial vision.